Personalidade e propensão à cirurgia plástica estética - Catia Fabiola Parreira de Avelar (2011)
The quick growth in the number of cosmetic surgeries done in the country and in the world, the constant presence of the theme in the media and the shortage of academic papers about the subject in the Brazilian context, caused the investigation of the consumers characteristics with a propensity to have this type of esthetic service that includes pain, high cost, modification of bodys parts and risks inherent in the surgical proceeding. This work proceeds from the assumption which great part of reactions standards of an individual can be predicted if the essential traits of personality and motivation of this individual are known. From academic papers that demonstrated that great part of the behavior can be related to the hierarchical structure of personality proposed by the Meta- Theoretic Model of Motivation and Personality -3M- (Mowen, 2000); the objective of this work is to discover which personality's traits, proposed by the 3M model, explain the propensity to undergo cosmetic surgery among students of a university located in Belo Horizonte. To reach such an objective, a descriptive research project was run using a survey with 697 undergraduate and graduate students. The results indicated that 37% of the behavior variance in the propensity to undergo cosmetic surgery can be explained by the proposed model. The scales used to measure the propensity to cosmetic surgery in the 3 M model: Openness to experience, Extraversion, Agreeability, Material needs, Body needs, Need for arousal, Self esteem, Competitiveness, Vanity view, Vanity concern ant Propensity to cosmetic surgery, showed satisfactory levels of validity and reliability, although all of the scales are susceptible to development. The scale Conscientiousness needs to be improved.